Comparison of Learning in Inductive and Deductive Approach to Increase Student’s Conceptual Understanding based on International Standard Curriculum (Jurnal Pendidikan IPA Indonesia, 2020)
This study aimed to determine the pattern of a more effective learning approach between the inductive and deductive approach in improving students’ conceptual understanding referring to the international standard curriculum on the X graders for the material property particulate subject matter. Through the deductive approach, students already have a picture/concept in their minds. But by using an inductive approach, students use their logic to understand concepts and summarize it. The research method applied in this study is a descriptive-comparative method with a triangulation analysis technique. Instruments used in the study were a questionnaire for the students, observation sheets, and three-tier diagnostic test items for pretest and posttest. The average pretest scores for deductive and inductive classes were 54.70 and 48.25, respectively. The result of the observation sheet analysis showed the deductive approach surpassed 12 points more than the inductive approach in improving the student’s learning activity. The result of the questionnaire analysis showed that 38 of 68 students prefer the learning process using deductive to inductive approach, and thought that it was suitable with the students’ characteristics. While the average posttest scores for deductive and inductive classes were 68.16 and 55.47, respectively. The analysis result of the N-Gain test towards the pretest and posttest results regarding the three-tier diagnostic test items indicated achievement of student’s conceptual understanding using a deductive approach which was 14.2225% higher than the use of the inductive approach. The Triangulation Analysis stated that the deductive approach was more effective in improving students’ conceptual understanding of Chemistry and material topics as well as material classification. While the inductive approach was more effectively applied to the topic of Particle Kinetic theory.